Lewis Acid Catalyzed 4π-Electrocyclization of Donor–Acceptor Stenhouse Adducts - Yoon, Seung Hyeon; Park, Kye Sung; Kim, Jaehee; Kwon, Yonghoon (Synthesis, 2023)
Lewis acid catalyzed 4π-electrocyclization of Donor–Acceptor Stenhouse Adducts (DASAs) has been developed. By employing catalytic quantities of Dy(OTf)3, a highly efficient transformation of acyclic DASAs into the corresponding cyclized isomers was achieved. Notably, this transformation exhibited exceptional yields, particularly in the case of first generation DASAs. In addition, Lewis acid catalysis enabled one-pot synthesis of the cyclopentenone product from the ‘donor’ and ‘acceptor’ components.
Keywords: Dy(OTf)3; furfural; secondary amine; photoswitch